BZD9L1 sirtuin inhibitor as a potential adjuvant for sensitization of colorectal cancer cells to 5-fluorouracil. (September 2019) - Tan, Yi Jer; Lee, Yeuan Ting; Petersen, Sven H.; Kaur, Gurjeet; Kono, Koji; Tan, Soo Choon; Majid, Amin M. S. Abdul; Oon, Chern Ein
Background: This study aims to investigate the combination effect of a novel sirtuin inhibitor (BZD9L1) with 5-fluorouracil (5-FU) and to determine its molecular mechanism of action in colorectal cancer (CRC). Methods: BZD9L1 and 5-FU either as single treatment or in combination were tested against CRC cells to evaluate synergism in cytotoxicity, senescence and formation of micronucleus, cell cycle and apoptosis, as well as the regulation of related molecular players. The effects of combined treatments at different doses on stress and apoptosis, migration, invasion and cell death mechanism were evaluated through two-dimensional and three-dimensional cultures. In vivo studies include investigation on the combination effects of BZD9L1 and 5-FU on colorectal tumour xenograft growth and an evaluation of tumour proliferation and apoptosis using immunohistochemistry. Results: Combination treatments exerted synergistic reduction on cell viability on HCT 116 cells but not on HT-29 cells. Combined treatments reduced survival, induced cell cycle arrest, apoptosis, senescence and micronucleation in HCT 116 cells through modulation of multiple responsible molecular players and apoptosis pathways, with no effect in epithelial mesenchymal transition (EMT). Combination treatments regulated SIRT1 and SIRT2 protein expression levels differently and changed SIRT2 protein localization. Combined treatment reduced growth, migration, invasion and viability of HCT 116 spheroids through apoptosis, when compared with the single treatment. In addition, combined treatment was found to reduce tumour growth in vivo through reduction of tumour proliferation and necrosis compared with the vehicle control group. This highlights the potential therapeutic effects of BZD9L1 and 5-FU towards CRC. Conclusion: This study may pave the way for use of BZD9L1 as an adjuvant to 5-FU in improving the therapeutic efficacy for the treatment of colorectal cancer.